Adaptación y propiedades psicométricas del inventario de ansiedad ante el desempeño musical de Kenny (IADM-K) - Chang Arana, Álvaro Mario (2015)
Music performance anxiety is a condition that affects instrumentalist musicians independently of gender, years of training, music style, etc.; and can deteriorate their professional development. Nevertheless, there are no specific tests for Peruvian music students. The aim of this research was to adapt and estimate the psychometric properties of the Kenny Music Performance Anxiety Inventory (K-MPAI) on a sample of 455 professional music students from three professional music institutions. After back translating the test, the author of the English test recognized it as the official Spanish version. Appropriate validity evidence based on test content was estimated by eight subject matter experts. Validity evidence based on internal structure was estimated by a second-order exploratory factor analysis with the Schmid-Leiman solution which showed a unidimensional structure (ordinal a = .97, SEM = 4.87). Additionally, two first order factors: “music performance anxiety” (ordinal a = .93, SEM = 6.11) and “depressive components” (ordinal a = .92, SEM = 3.01) were identified. Based on the new structure, a Negative Affectivity Towards Music Performance Inventory (NAMPI) was proposed. Finally, with a p < .001, the K-MPAI presented high and significant correlational values with STAI and BAI and, thus, appropriate validity evidence based on the relation with other variables. Results showed that interpretations and decisions based on the scores obtained through the adaptation of the K-MPAI present validity and reliability evidence for professional music students of Metropolitan Lima.